2016
DOI: 10.1016/j.marpolbul.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical systems perspective for a real-time response to a marine oil spill

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractThis paper discusses the combined use of tools from dynamical systems theoryand remote sensing techniques and shows how they are effective instruments which may greatly contribute to the decision making protocols of the emergency services for the real-time management of oil spills. This work presents the successful interplay of these techniques for a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 46 publications
2
34
0
1
Order By: Relevance
“…It also applies to both Hamiltonian and non-Hamiltonian systems 52 as well as to stochastic dynamical systems 53 . Moreover, Lagrangian descriptors can be applied directly to data sets obtained from the numerical solution of geophysical models and satelite observations [54][55][56] . We provide more details on our use of Lagrangian descriptors in Appendix A.…”
Section: Introductionmentioning
confidence: 99%
“…It also applies to both Hamiltonian and non-Hamiltonian systems 52 as well as to stochastic dynamical systems 53 . Moreover, Lagrangian descriptors can be applied directly to data sets obtained from the numerical solution of geophysical models and satelite observations [54][55][56] . We provide more details on our use of Lagrangian descriptors in Appendix A.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbation of the cat eyes results in irreversible deformation of material contours, signifying Rossby wave breaking. de la Cámara et al (2013) and Guha et al (2016) identified HTs both within and outside the SPV, thus suggesting that Rossby wave breaking can occur in either of those regions. The former authors worked with reanalysis data, while Guha et al (2016) used a dynamical model based on the shallow-water equations in which the perturbing waves are produced in a controlled manner.…”
Section: Will Ozone Depletion Extend Worldwide?mentioning
confidence: 98%
“…The function M has been applied in a variety of geophysical contexts. For example, in the ocean, it has been used to analyse the structure of the Kuroshio current (Mendoza and Mancho, 2012), to discuss the performance of different oceanic data sets (Mendoza et al, 2014), to analyse and develop search and rescue strategies at sea (García-Garrido et al, 2015) and to efficiently manage in real time the environmental impact of marine oil spills (García-Garrido et al, 2016). In the field of atmospheric sciences, M has been used to study transport processes across the southern SPV and RWB de la Cá-mara et al, 2012Cá-mara et al, , 2013Smith and McDonald, 2014;Guha et al, 2016 and to investigate the Northern Hemisphere major stratospheric final warming in 2016 (Manney and Lawrence, 2016).…”
Section: Lagrangian Descriptorsmentioning
confidence: 99%